2022
DOI: 10.1177/10775463221077779
|View full text |Cite
|
Sign up to set email alerts
|

Vibration suppression and energy absorption of plates in subsonic airflow using an energy harvester enhanced nonlinear energy sink

Abstract: In this paper, a nonlinear energy sink (NES) and a giant magnetostrictive-piezoelectric (GMP) energy harvester (NES-GMP) are investigated to suppress the nonlinear aeroelastic responses and to absorb the mechanical energy of an embedded plate interacting with external subsonic airflow. The analytical model of the embedded plate attaching the NES-GMP is established by using the Hamilton’s principle based on the Kirchhoff plate theory and incompressible subsonic aerodynamic model. The natural frequencies of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Also, the NES mass needs to be controlled at 10-15% of the airfoil mass [174]. The NES-giant magnetostrictive-piezoelectric also performs International Journal of Energy Research well in suppressing nonlinear aeroelastic response and harvesting energy [175]. NES-giant magnetostrictive-piezoelectric has also been applied to the subsonic aeroelastic system, where the energy harvesting performance of the system is affected by periodic motion and instability [176].…”
Section: Piezoelectric Energy Harvestermentioning
confidence: 99%
“…Also, the NES mass needs to be controlled at 10-15% of the airfoil mass [174]. The NES-giant magnetostrictive-piezoelectric also performs International Journal of Energy Research well in suppressing nonlinear aeroelastic response and harvesting energy [175]. NES-giant magnetostrictive-piezoelectric has also been applied to the subsonic aeroelastic system, where the energy harvesting performance of the system is affected by periodic motion and instability [176].…”
Section: Piezoelectric Energy Harvestermentioning
confidence: 99%
“…The conclusion demonstrated that NES could immediately restrain the system response during the initial stages of vibration and shock. Furthermore, this control strategy has been extended to practical applications for vibration reduction purposes in recent years, including but not limited to beams (Ahmadabadi and Khadem, 2012; Zhao et al, 2022), energy harvesting (Li et al, 2017; Zhang et al, 2019; Yao and Qiao, 2022), spacecraft (Zhang et al, 2019), airfoil structure (Guo et al, 2013; Lee et al, 2010), turbine motor (Aghayari et al, 2021), and other systems (Bergeot et al, 2017).…”
Section: Introductionmentioning
confidence: 99%